Predicting Posttraumatic Stress Symptoms From Pretraumatic Risk Factors: A 2-Year Prospective Follow-Up Study in Firefighters - Heinrichs, Markus; Wagner, Dieter; Schoch, Walter; Soravia, Leila M.; Hellhammer, Dirk H.; Ehlert, Ulrike (The American journal of psychiatry, 2005)
OBJECTIVE: Most studies focusing on risk factors for posttraumatic stress disorder (PTSD) have used retrospective study designs. Only a small number of studies have prospectively examined risk factors in the immediate aftermath of trauma exposure in predicting PTSD symptoms. The purpose of this study was to identify predictive risk factors for posttraumatic stress symptoms and comorbid psychopathological symptoms present during the time before exposure to traumatic stress in a high-risk population. METHOD: Forty-three professional firefighters were assessed immediately after basic training (baseline) and at 6, 9, 12, and 24 months after entry into firefighter service. Subjects were screened for psychopathological symptoms, including symptoms of PTSD, depression, and anxiety. Subjects were also characterized with regard to personality traits such as self-efficacy, hostility, and alexithymia. Neuroendocrine activity was assessed by examination of awakening and diurnal salivary cortisol profiles and 24-hour urinary catecholamine excretion. Multiple linear regression analysis was used to analyze posttraumatic stress symptoms at 24-month follow-up as a function of pretraumatic characteristics. RESULTS: A high level of hostility and a low level of self-efficacy at baseline accounted for 42% of the variance in posttraumatic stress symptoms after 2 years. Subjects who had both risk factors at baseline showed a significant increase in measures of PTSD symptoms, depression, anxiety, general psychological morbidity, global symptom severity, and alexithymia during the 2-year period. Biological characteristics were not predictive of the development of psychopathological symptoms. CONCLUSIONS: These results suggest that specific personality traits may constitute markers of vulnerability to the development of psychopathological symptoms after trauma exposure. Early identification of preexisting risk factors is needed to provide effective prevention and intervention for individuals who are at risk of developing trauma-related disorders.